Gadai Dalam Konteks Hukum di Indonesia - Amalia, Dita Nofa; Musaffak, Fattoriqul; E, Elisa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The importance of assessing the effectiveness of pawning as collateral in various economic and legal situations. For some time, pawning has been used as a method of providing credit that involves the surrender of goods as collateral for debt. However, its relevance in facing the challenges of modernizing the financial system still needs to be reviewed. This study uses qualitative methodology by conducting case studies at financing institutions and conducting in-depth interviews with stakeholders, including pawners and customers. By using thematic analysis, the data is evaluated to find elements that influence the effectiveness of pawning, such as regulations, ease of access, and legal protection. The results of the study show that pawning remains a useful tool for collateral, especially for lower-middle economic communities who do not have access to formal financial services. However, public awareness of the pawn process, applicable regulations, and rules of related institutions affect this performance. So, to improve the function of pawns as a flexible and inclusive collateral tool, it is necessary to strengthen regulations and public education.